Static and Dynamic Balance and Injury Prevalence in Snowboard Instructors - Anike Vanagas; Vilma Dudonienė (Lithuanian Sports University, 2022)
Background. Snowboarding is a quite popular winter sport, though associated with the risk of injury. Aim: to determine the relationship between sport injuries and static and dynamic balance in snowboard instructors. Methods. The study included snowboard instructors from Ontario, Canada. Questionnaires were given before and after the winter season to obtain injury history. Static balance was evaluated with a Wii Balance Board. Dynamic balance was evaluated using the Y balance test. The results were compared between different genders, age and days on-snow per season. Results. Male snowboard instructors had, on average, higher static balance scores than the females. Both male and female scores for testing with eyes closed were significantly lower than with eyes open. The female snowboard instructors had, on average, higher dynamic balance scores than the males. However, for eyes closed testing, female snowboarders' scores were noticeably better than the males' scores. Nine of out twenty snowboard instructors had sustained one or more injuries in the past snowboarding season. One female and one male sustained two injuries each, and in total there were ten injuries amongst twenty snowboarders. Conclusions. There was no significant difference between prevalence of injury and balance amongst different genders. Keyword: snowboarding, sports injuries, static balance, dynamic balance.